Advance rulings and binding pre-entry tariff classification according to Article 3 TFA: Situation 2018 - still a long way to go - Carsten Weerth (World Customs Journal, 2018)
Article 3 of the World Trade Organization (WTO) Trade Facilitation Agreement (TFA) requires each TFA member to issue advance rulings in a reasonable time that are binding on the applicant and the customs authorities of the issuing country. Such binding advance rulings cover, among other things, tariff classification information that is crucial for the calculation of import duties and tariffs. This paper investigates which countries are offering advance tariff classification rulings and which are still not offering such rulings and finds that, in 2018, 72 countries are offering binding pre-entry customs classification. However, without the European Union (EU) member states, only 44 harmonised system member states out of 157 are offering these binding pre-entry customs classifications. Fifty-nine countries that are offering advance rulings on tariff classification have ratified the TFA, but 16 countries are offering this service without having ratified the TFA.
Keywords: K33; K34; 330; Customs Law; International Law; WTO; Trade Facilitation Agreement; Harmonized System; Customs Classification